PENGARUH PENYULUHAN DENGAN BOOKLET TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PRAKTIK HIGIENE PERORANGAN PADA PENJAMAH MAKANAN - Ulya Rahmawati; Dyah Nur Subandriani; Yuniarti Yuniarti (Poltekkes Kemenkes Semarang, 2020)
Background: Hygienic and healthy food has become the principle of Food Service. Based on POM RI data in 2015, the causes of Food Poisoning Outbreak on catering services in 2015 were 13 incident (21.31%). This outbreak was happened because of knowledge, attitudes and practices personal hygiene of food handlers were poor.Objective: To analyze the effect of mass-education with booklets on knowledge, attitudes, and practices of personal hygiene among food handlers at J Catering Service Semarang.Method: This study was pre-experiment with one group pretest-posttest design. The sampling technique was used total sampling method with the study subjects were 12 food handlers at J Catering. Data collection were included knowledge, attitudes and practices. The data were analyse by Paired T-test and Wilcoxon test to determine the increase of knowledge, attitudes and practices of food handlers before and after given education about personal hygiene.Result: There were differences in knowledge and practice of personal hygiene before and after education (p = 0.002). There was no difference in attitudes of personal hygiene before and after education (p = 0.059).Conclusion: Education using booklets has been able to increase knowledge and practices personal hygiene of food handlers.